Reader's guide to the history of science - Hessenbruch, Arne (Fitzroy Dearborn, 2000)
"A readers' advisory to the best books on the history of science. Written by 200 international scholars, the 600 comparative essays begin with a bibliography of important works, followed by reviews of those sources in the body of the entry. Important concepts and processes, phenomena, and scientists as well as scientific developments in different countries are covered."--"Outstanding Reference Sources," American Libraries, May 2002